-26=2y+4(y+7)

Simple and best practice solution for -26=2y+4(y+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -26=2y+4(y+7) equation:


-26=2y+4 (y+7)

We simplify the equation to the form, which is simple to understand
-26=2y+4(y+7)

Reorder the terms in parentheses
-26=2y+(+4y+28)

Remove unnecessary parentheses
-26=+2y+4y+28

We move all terms containing y to the left and all other terms to the right.
-2y-4y=+28+26

We simplify left and right side of the equation.
-6y=+54

We divide both sides of the equation by -6 to get y.
y=-9

See similar equations:

| 17=k+4 | | x=-3(x+n) | | 14a+-93=49+57a | | -10=8-x*7 | | -21=7u+7(u-7) | | 3(6z+7)+10z+45=180 | | 4x^2-7x-57=0 | | (2x-30)=45 | | (x^2-1)=0 | | w-16=-3 | | x+(x+4)=50 | | 4x-19=13x-1 | | 2(x-6)=7 | | 3(6z+7)10z+45=180 | | 2/3(3x+1)=5 | | -1.25+0.5x=0 | | 9x-7=12x-4 | | 3x*3y= | | 20+8(a-11)=-12 | | 9x-7=12-4 | | x^2+8xy+16y^2-4x-16y+7=0 | | -3(2x+3)=-6x+9 | | f(-1.5)=3x^2-6x+3 | | x-11(13+4x)=-3(5-9x)+2 | | 3x+2=9x+6 | | (x-3).4=8 | | 8(3x-2y)+4[(-3x)+4y]= | | 5x-4=8x+5 | | 2.35(4x-4)=-2+10x+12 | | x+23=69 | | 5n-3[n-5]=13 | | 11x+3=9x-11 |

Equations solver categories